La fecundidad en la ciudad de Rosario, Argentina: proyecciones y retroproyecciones de la tasa global de fecundidad y las tasas específicas de fecundidad - Lucía Andreozzi (Centro Centroamericano de Población, 2021)
The study that gives rise to this article arises from the results obtained in the framework of a collaboration agreement signed by the Statistical Office of Rosario City and the School of Statistics of the Faculty of Economic Sciences and Statistics (National University of Rosario). Among its objectives is to obtain probabilistic fertility forecasts for Rosario City. For this, based on vital statistics, estimates and population projections, probable scenarios, past and future, are constructed, both for the global fertility rate and the specific fertility rates. The results of this study, based on the application of probabilistic prognostic models, allow to know structures and trends, past and future, of fertility, so that diagnoses can be generated that are useful for the evaluation and management of the health system or good for the development of new public policies. The results indicate that Rosario had, has and will continue to have a change in fertility patterns faster and more marked than the national average. Although this fact is to be expected in a context marked by advances in public health (which allow access to more and better reproductive health care), the methodology used here is based solely on the extrapolation of trends, therefore, the backprojection must be carefully analyzed.